PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL TERHADAP HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR PADA PEMBELAJARAN IPS - Luthfi Indah Setyani; Endang Wahyudiana; Yustia Suntari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This quasi-experimental research examines the effect of using the interactive learning media Wordwall on the social studies learning outcomes of third-grade elementary school students. The study was conducted at SDN Jatibening II with two groups: an experimental group using Wordwall and a control group using conventional textbooks. Data were collected through validated pre-test and post-test instruments. Normality and homogeneity tests indicated that the data met statistical assumptions. The independent sample t-test showed a significance value of 0.005 (< 0.05), indicating that Wordwall had a significant positive effect on students’ learning outcomes. The results suggest that Wordwall effectively increases students’ engagement and cognitive achievement in social studies learning.